Analysis of Factors Influencing Banks’ Intermediation Functions (A Case Study on Conventional Digital Banks Listed on the IDX) - Auditia, Zerlinda Luna; Vietha Devia SS (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The advancement of technology has brought innovation to banking by forming a digital bank. Digital banks are banks that provide transaction services through electronic channels without physical offices. Digital banks have a function and role as an intermediary institution that is important to be implemented properly so that there is fluency in payment traffic and money circulation. The purpose of this study is to analyze the factors that affect the intermediary function of digital banking in Indonesia listed on the Indonesia Stock Exchange (IDX). This research is quantitative type with secondary data using panel data regression analysis method. The samples in this study are AGRO, AMAR, ARTO, BBHI, BBSI, BBYB, BTPN, and DNAR. The dependent variable used is LDR, then the independent variables in this research are internal factors represented by CAR (X1) and NPL (X2), as well as external factors represented by Inflation (X3) and Internet Access (X4). The result of the findings in the study shows that the variables of CAR, NPL, and Internet Access have a significant positive effect on LDR, while Inflation does not have a significant effect on LDR.